Public Accounting and Business Accounting: Two Different Upstream - Irwan Taufiq Ritonga (Journal of Accounting and Investment, 2020)
Research aims: This article is a persuasive essay, written with motivation to change readers' perceptions of accounting for public organizations, especially government organizations. This article aims to provide arguments following detailed explanations that accounting of public organization and accounting of business organization stand on two different accounting-world.Design/Methodology/Approach: This article is a persuasive essay.Research findings: The differences between the two have started since the beginning of the formation of each organization, namely differences in motives and backgrounds of the formation of the organization, goals of the organization's establishment and how to achieve organizational goals, as well as the source and nature of organizational funding.Theoretical contribution/ Originality: These differences in the upstream give consequences differences in downstream, which are significant dissimilarities between the two accounting worlds on planning and budgeting aspects, financial reporting systems (financial accounting), managerial accounting, and auditing.Practitioner/Policy implication: This significant difference in accounting education implies that the curriculum of accounting education must be reconsidered by separating the public accounting curriculum and the business accounting curriculum.